Challenges of Online Learning During the Covid-19 Pandemic in Madrasah - Mohammad, Mohammad (Universitas Nurul Jadid, 2021)
This study aims to analyze the optimization of online learning based on parental involvement in madrasas during the Covid-19 pandemic. This research uses the descriptive qualitative method of case study type. Data collection techniques are carried out through observation, interviews and documentation. The data analysis technique is carried out through data collection, reduction, presentation, and conclusion. The results of the study show that the challenges of online learning implemented during the Covid-19 pandemic include the readiness that educators must have, student factors and geographical challenges. This research provides implications for the importance of learning designs that teachers in online learning activities must make to perfectly realize educational and learning objectives.